Delafossite type CuCo0.5Ti0.5O2 composite structure: A futuristic ceramics for supercapacitor and EMI shielding application. Issue 7 (1st April 2021) - Bhattacharya, Debopriya; Ghoshal, Debopriyo; Mondal, Dheeraj; Paul, Biplab Kumar; Pal, Joydeep; Gupta, Bhaskar; Bose, Navonil; Nandy, Papiya; Basu, Mousumi; Das, Sukhen
Abstract: Cu-based delafossite type CuCo0.5 Ti0.5 O2 composite structure has been synthesized via a simple chemical synthesis technique followed by a high-temperature sintering process. Structural investigations on the synthesized sample have been carried out by using XRD, FT-IR, and Raman spectroscopy techniques. Optical spectroscopy (UV–Vis and photoluminescence) study reveals beneficial information about the bandgap (Eg ) and defect state density of CuCo0.5 Ti0.5 O2 composite structure, explaining the superior electrochemical and microwave shielding performance of the composite structure. Cyclic voltammetry and galvanostatic charge-discharge measurement within the potential window of −0.5 V to +0.4 V illustrate the pseudocapacitive nature of the sample with a specific capacitance value of ~ 283 F g -1 at a current density of 0.5 A g -1 which can retain up to ~ 86% of its original value after 2000th cycle. A 400 μm thin sample made of CuCo0.5 Ti0.5 O2 composite structure is capable to shield up to ~ 58 dB of incident electromagnetic (EM) wave energy at 16.5 GHz wavelength with absorption efficiency of ~ 52.5 dB. The electromagnetic interference (EMI) shielding effectiveness (SE) is found to be ~ 99.999% against the harmful electromagnetic interference in the 8–12 GHz frequency region.